Sjögren’s syndrome associated with systemic lupus erythematosus - Taşdemir, Mehmet (Turk Pediatri Ars, 2016)
Systemic lupus erythematosus and Sjögren’s syndrome are chronic auto- inflammatory disorders which can lead to serious organ damage. Although systemic lupus erythematosus and Sjögren’s syndrome were previously considered two forms of the same disease because of presence of clinical coexistence of these two conditions, the view that they are two different conditions with mutual characteristics has become prominent in recent years. In this paper, we reported a 16 year-old girl who was followed up with a diagnosis of Sjögren’s syndrome for six years and then was observed to have overlap of systemic lupus erythematosus. In the baseline, she did not have any clinical or serological evidence for systemic lupus erythematosus. After six year, massive proteinuria and serological findings developed and systemic lupus erythematosus nephritis was diagnosed by kidney biopsy. Currently, systemic lupus erythematosus and Sjögren’s syndrome cannot be differentiated definetely. We need more valuable diagnostic and classification criteria to differentiate these two important conditions.